Higher Education Social Engineering Attack Scenario, Awareness & Training Model (Journal of The Colloquium for Information Systems Security Education, 2020)
In today’s information security ecosystem, hackers and threat actors are increasingly using social engineering tactics to circumvent advanced technical security technologies. While every year there are vast leaps in technical security systems, one critical dynamic, the human psychology still needs a dire upgrade to their operating system. The human dynamic and our innate psychological processing algorithms need a new approach to mitigate social engineering attacks. Higher education institutions are prime target for social engineering engagement missions as they house a large diverse population of faculties, students, alumni, and employees in their ecosystem. This diversity paired with increasing inclusion of international individuals only expands the existing dynamic vulnerable landscape, thereby requiring innovative methods to secure it. In this paper, the authors utilize an existing framework to develop nine specialized and publicly available social engineering attack scenarios geared toward a higher education environment. The paper also proposes preliminary models for social engineering awareness and training to combat such attacks. The effectiveness of the proposed models will be assessed by comparing pre- and post- awareness surveys as part of the future work.
Keywords: information security; social engineering; social engineering attack scenario; social engineering awareness model; social engineering training model; social engineering ethics